The archaeology of removal in North America - Weik, Terrance M. (University Press of Florida, 2019)
This edited volume brings together people seeking to understand what happens when human beings are forced out of their homes, and away from their usual places of work, play, worship, and well being. It illustrates how archaeologists are situated among the anthropologists and other scholars who are investigating the catalysts, dynamics, and meanings of removal.